Assessing Pedestrian Facilities for the Blind in the Urban Environment of an Emerging Economy - Liyana, Mohamed Yusof; Shaliha, Minhad; Noor Asiah, Mohamad; Nurhidayah, Azmy (Penerbit UMP, 2021)
In highlighting the sustainable urban environment of an emerging economy, walkability becomes a key trait. The criteria that can improve walkability in urban areas are the provision and ease of access to pedestrian facilities for everyone, including people with disabilities (PWDs). The mobility of PWDs in urban areas is very challenging as they face physical, cultural, and social barriers that hinder their participation in society. In line with this concern, this study intends to assess the current provision and accessibility aspect of pedestrian facilities for the blind in Kuantan city by using on-site assessment. The findings reported that the pedestrian facilities for the blind in Kuantan city are lacking in the provision and not entirely accessible specifically on walkway/sidewalk, tactile block, pedestrian crossing, handrail, and ramp. The barriers underlined in the findings may act as a direction for local authorities and industry to improve the pedestrian facilities for the blind and, consequently, will be equally beneficial for all pedestrians.